Buckling Analysis for Flexspline Structure in Harmonic Drive with FEM - Zhang Qingru; Huang Dishan; Gu Jingjun (Jixie chuandong)
By using the function of eigen buckling in ANSYS,the torsional buckling problem of flexspline in a harmonic driver is analyzed. Through changing the structure parameter of two kinds of flexspline,the corresponding critical instability torque under each structure parameter is investigated. The research results show that the mode shapes of torsional buckling are close to that of the actual instable failure,and computation result is good agreement with engineering problem. So the torsional buckling check will be valuable in the flexspline structure of harmonic reducer.